Me Evaluasi Aplikasi Santi Padu Sebagai Upaya Optimalisasi Pelayanan Kesehatan di RSUD Klungkung - Ayu Mas Rani Ardana Ni Nyoman; Lilik Antarini; Dewa Ketut Suryawan (Journal of Contemporary Public Administration, 2025)
Santi Padu is a technology-based innovation program designed to minimize the accumulation of patients and speed up the administrative process at Klungkung Hospital through an online queue system, especially registration to the polyclinic related to complaints that occurred previously, namely the accumulation of the number of patients, the difficulty of registering at the registration counter, the length of time to get information about the laboratory and the place to complain. This study aims to evaluate the application of Santi Padu in optimizing health services, using a descriptive qualitative approach research method with data collection techniques such as observation, interviews, and documentation. Interviews were conducted with informants who were directly involved in the implementation of the Santi Padu application at Klungkung Hospital, namely the Plt. Program Development Division of Klungkung Hospital, registration counter officers, and also the community as application users. The evaluation was carried out based on six indicators of public policy evaluation, according to William Dunn, namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results of the study showed that the Santi Padu application was effective in reducing patient waiting time, with an average reduction in service time. The app is also efficient in resource usage, minimizes operational costs, and simplifies administrative processes. In terms of adequacy, features such as online registration, bed availability information, and complaint services have helped improve the quality of service. In terms of equity, this application provides equal access to people in all Klungkung areas with internet support, including remote areas. The responsiveness of Klungkung Hospital to community complaints is quite good, with a special team that handles complaints quickly. In addition, this application is considered right on target in solving major problems such as the accumulation of patients at the registration counter. Based on these findings, it can be concluded that the Santi Padu application has a positive impact on improving health services so that it can be used as a model for health service innovation in other regions, although further development and the addition of other features are needed.